A Calcar Collar Is Protective Against Early Torsional/Spiral Periprosthetic Femoral Fracture: A Paired Cadaveric Biomechanical Analysis. (19th August 2020) - Johnson, Aaron J.; Desai, Shivam; Zhang, Chunyang; Koh, Kyung; Zhang, Li-Qun; Costales, Timothy; O'Toole, Robert V.; Manson, Theodore T.
Abstract : Background: Periprosthetic fracture is a leading reason for readmission following total hip arthroplasty. Most of these fractures occur during the early postoperative period before bone ingrowth. Before ingrowth occurs, the femoral component can rotate relative to the femoral canal, causing a spiral fracture pattern. We sought to evaluate, in a paired cadaver model, whether the torsional load to fracture was higher in collared stems. The hypothesis was that collared stems have greater load to fracture under axial and torsional loads compared with collarless stems. Methods: Twenty-two cadaveric femora (11 matched pairs) with a mean age of 77 ± 10.2 years (range, 54 to 90 years) were harvested. Following dissection, the femora were evaluated with use of a dual x-ray absorptiometry scanner and T scores were recorded. We utilized a common stem that is available with the same intraosseous geometry with and without a collar. For each pair, 1 femur was implanted with a collared stem and the contralateral femur was implanted with a collarless stem with use of a standard broaching technique. A compressive 68-kg load was applied to simulate body weight during ambulation. A rotational displacement was then applied until fracture occurred. Peak torque prior to fracture was measured with use of a torque meter load cell and data acquisition software. Results: The median torque to fracture was 65.4 Nm for collared stems and 43.1 Nm for uncollared stems (p = 0.0014, Wilcoxon signed-rank test). The median T score was –1.95 (range, –4.1 to –0.15). The median difference in torque to fracture was 29.18 Nm. As expected in each case, the mode of failure was a spiral fracture around the implant. Conclusions: Collared stems seemed to offer a protective effect in torsional loading in this biomechanical model comparing matched femora. Clinical Relevance: These results may translate into a protective effect against early periprosthetic Vancouver B2 femoral fractures that occur before osseous integration has occurred.